Operator's whole body vibrations dependent of agrotechnical surface, speed of movement and seat upholstery - Barač, Željko; Plaščak, Ivan; Jurić, Tomislav, agronom; Jurišić, Mladen; Zimmer, Domagoj; Vidaković, Ivan, inženjer strojarstva; Petrović, Davor, agronom; Duvnjak, Vinko; Marković, Monika (2018)
The paper presents the recorded vibrations that affect the operator’s body when an agricultural tractor moves along three types of agrotechnical surfaces, i.e. asphalt, an alfalfa field, and a field path, and when seven different tractor seat upholsteries are used. The research was performed in accordance with the HRN ISO 2631-1 and HRN ISO 2631-4 standards. The tractor used in the research was an IMT 560 and the duration of the measurement was 30 minutes, which was repeated three times for every tractor seat upholstery type. The research was exploitative. The measurements were performed using an MMF VM30 meter. The paper reveals a different level of vibrations in dependence with different surfaces and seat upholsteries. The fewest vibrations were produced by asphalt, and the best upholsteries are memory foam and sponge.
Bibliografija: 14 jed.
Abstract.
Keywords: Traktori -- Vozači traktora -- Vibracije -- Agrotehničke površine -- Presvlake sjedala